Peran Perceived Social Support Terhadap Parenting Stress pada Ibu yang Memiliki Anak ASD di Sekolah ‘X’ Bandung - Aprilia Liestiany Kuswandy; Priska Analya (Humanitas (Jurnal Psikologi), 2025)
This study aims to determine the role of perceived social support in relation to parenting stress among mothers of children with autism spectrum disorder (ASD) at School “X” in Bandung. This study employed a quantitative correlational design with purposive sampling, resulting in 24 mothers of children with ASD at School “X” in Bandung as participants. The perceived social support measurement tool based on Sarafino theory, consistingg of 28 items. The Parenting Stress measurement tool using the Paremting Stress Index–Short Form (PSI-SF), which consists of 36 items. The results of the research using a simple linear regression test showed a simultaneous significance value of 0.00, which means that perceived social support plays a significant role in parenting stress. Perceived social support contributes 13.6% to the variance in parenting stress, while 86.4% is influenced by other factors. For other researchers, they can consider or increase the sample size in order to conduct an analysis by type (partial) to complete the data on the contributions of each type and to investigate other factors, such as resilience, that can reduce parenting stress.